Steady-state flow computation in gas distribution networks with multiple pressure levels. (15th February 2017) - Cavalieri, Francesco
Abstract: Natural gas networks are critical lifelines essential to the continued well-being of a community. Whatever its scope, the analysis of a gas network cannot rely on simple connectivity methods: limited tolerance on quantity and quality (pressure) to maintain serviceability to end-users generates the need for a flow analysis. Scarceness of the literature on flow analysis for gas networks and limitations of the available methods prompted this work. A novel complete steady-state flow formulation is reported, up to the governing nonlinear system of equations and the expression of the error function to be minimised to find the solution. Important features, such as the correction for elevation change in pipes and the pressure-driven mode, are included. The possibility to treat multiple pressure levels, as is the case of real networks, represents the main novelty of this work. The presented procedure was coded into a programming language and applied to several test cases, one of which being a non-trivial realistic gas network with 67 nodes and 88 edges. Such examples served the purpose to validate the formulation and to show its computational performance in the presence of multiple pressure levels. Highlights: The computation of the operational state of gas distribution networks is crucial. A steady-state flow formulation with multiple pressure levels is proposed. The formulation is pressure-driven, essential in network assessment problems. The correction for elevation change in pipes is taken into account. The formulation is able to handle non-trivial realistic gas networks.